Brain γ‐aminobutyric acid: a neglected role in impulsivity. (27th January 2014) - Hayes, Dave J.; Jupp, Bianca; Sawiak, Steve J.; Merlo, Emiliano; Caprioli, Daniele; Dalley, Jeffrey W.
Abstract The investigation of impulsivity as a core marker of several major neuropsychiatric disorders has been greatly influenced by the therapeutic efficacy of drugs that block the reuptake of dopamine and noradrenaline in the brain. As a result, research into the neural mechanisms of impulsivity has focused on the catecholamine systems as the loci responsible for the expression of impulsive behaviour and the primary mechanism of action of clinically effective drugs for attention‐deficit hyperactivity disorder (ADHD). However, abnormalities in the catecholamine systems alone are unlikely to account for the full diversity and complexity of impulsivity subtypes, nor can they fully explain co‐morbid brain disorders such as drug addiction. Here we review the lesser‐studied role of γ‐aminobutyric acid (GABA) in impulsivity, a major target of the dopaminergic and noradrenergic systems in the prefrontal cortex and striatum, and consider how abnormalities in this inhibitory neurotransmitter might contribute to several forms of impulsive behaviour in humans and experimental animals. Our analysis reveals several promising leads for future research that may help inform the development of new therapies for disorders of impulse control.